FEATURES OF ANGENESIS AGAINST THE BACKGROUND OF NEGATIVE PRESSURE WOUND THERAPY IN PATIENTS WITH NEUROPATHIC AND NEUROISCHEMIC FORMS OF DIABETIC FOOT ULCERS - E. L. Zaitseva; L. P. Doronina; R. V. Molchkov; I. A. Voronkova; V. A. Mitish; A. Yu. Tokmakova (Вестник хирургии имени И.И. Грекова)
The authors analyzed clinical (size, tissue oxygenation), histological (light microscopy) and immunohistochemical (CD68, MMP-9, TIMP-1) features of reparative processes of soft tissue of lower extremities in patients with diabetes mellitus against the background of vacuum therapy in comparison with standard local treatment. Patients (31 cases) with diabetic foot ulcers were followed-up after surgical d-bridement and before plastic closure of the wound. During perioperative period 13 patients obtained the negative pressure wound therapy (NPWT of 90-120 mmHg) and 18 patients had the standard care. Given results supported higher efficacy of NPWT as compared with standard local care. The therapy caused rapid reduction of wound and its depth, increased local microcirculation and reduced inflammation. These data were confirmed by the histological and immunohistochemical studies. The high efficacy of the method of local treatment could significantly reduce the time of wound preparation for the next step of surgical treatment.